UKRAINIAN STARTUPS IN THE CONDITIONS OF WAR - Кудельський, Віталій (SWorldJournal, 2024)
The role and significance of startups for the innovative development of the state has been studied. The impact of the war on the development of startup markets in Ukraine was studied. The main goals and tasks faced by the launches during the war were stud